BIOIMPEDANCE ANALYSIS AS A DIAGNOSTIC TOOL FOR METABOLIC RISK FACTORS SCREENING - Каширина, Елена Жоржевна; Маклакова, Татьяна Петровна; Жилина, Наталья Михайловна; Тинькова, Наталья Юрьевна (Medicine in Kuzbass, 2025)
The problem of obesity and associated metabolic disorders requires the attention of specialists of various profiles, especially at the level of primary health care. The development of effective methods for early diagnosis of metabolic risk factors is relevant. The aim of the study was to evaluate the effectiveness of bioimpedance analysis (BIA) in the diagnosis of metabolic risk factors in patients with different degrees of obesity. Materials and Methods. The analysis of BIA data of 218 people (19-86 years old) performed with the help of ABC-01 «Medass» analyzer at the frequency of 50 kHz according to the standard tetrapolar scheme was carried out. Statistical processing was performed using IBM SPSS-22 and MS Excel-13 programs. Results. Significant correlations were revealed between body mass index (BMI) and water balance indices: extracellular water (ρ = 0.77), total water (ρ = 0.73) and intracellular water (ρ = 0.69). The most pronounced differences between risk groups were obtained for BMI (χ² = 118.7; p < 0.001), fat mass (χ² = 101.5; p < 0.001) and lean mass (χ² = 79.4; p < 0.001). Conclusion. BIA demonstrates high diagnostic value in the assessment of fat component, muscle-cell composition and water balance. The combined use of BMI and waist/hip index improves the accuracy of metabolic risk prediction compared to their isolated use.